Pronunciation in the Study of French: Attitudes of Teacher-Trainees in Colleges of Education in Ghana - Fiadzawoo Jonas Kwabla; Yegblemenawo Stella Afi Makafui; Quansah Joseph Yaw Dwamena (European Scientific Journal, ESJ, 2017)
This study aims at finding out the attitudes of teacher trainees in selected colleges of education in Ghana towards the learning of French language pronunciation. To achieve this aim, Pronunciation Attitude Inventory (PAI) was used to collect field data from 229 French teacher trainees purposively selected from the five colleges of education responsible for training French teachers in Ghana. The participants were asked to respond to PAI comprising 13 statements on the five-point Likert scale. This was intended to elicit their views on the learning of pronunciation which has been introduced into their curriculum. The results which were analysed by the use of SPSS indicated that the teacher trainees have good attitudes towards the learning of pronunciation in the French language. It is believed that the trainees would in turn teach pronunciation after their graduation as French teachers. The article concludes with a suggestion to language teachers as well as curriculum planners to include components of pronunciation in language courses and help students to acquire correct pronunciation of words since this enhances mutual intelligibility in terms of communication.